Opodatkowanie a rentowność branży niskiego hazardu - Skłodowski, Ireneusz (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The article defines the profitability of low gambling. Setting the tax on gambling at the level of 2000 zł will cause lowering of the profitability of low gambling. Remaining profitability is possible at the tax on gambling lower than 1900 zł. The optimal tax rate should be set at 1500 zł. It would allow to gain the budget profit of 590 mln zł.